Strategic Hedging in ASEAN: A Response to the Rise of (Beijing and) Washington - Santoso, Yulida Nuraini (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2024)
This article problematizes three predominant narratives surrounding the behavior of ASEAN member states and the rivalry between Beijing and Washington in the context of ASEAN’s political security. This qualitative research is developed through a mixed assessment of documents, archive, and literature reviews combined with behavioral and contextual observations. Firstly, it questions the narrative of the ‘assertiveness’ of China as a rising power. With close trading relations dating back to the first dynasties, this Paper argues that the notion of China’s assertiveness and aggression is misplaced. As a key regional trade partner, China was never a threat to ASEAN countries. This narrative developed with the growing interest of the United States to contain the region from China over the years. As such, there lies a gap in the literature, which leads to the singling out of narratives that better explain the holistic relation between ASEAN states and China. Secondly, this article surfaces the lack of consistent commitment of the US to the Asia Pacific (also referred to as the ‘Asia Pivot’), other than to signify its interest in aggressively preventing China from dominating the Indo-Pacific. In this sense, the US’ behavior is viewed less as a great power but more as a greatly reactive one. Lastly, hedging is analyzed here as a necessary response to the dynamics of the Indo-Pacific arena and not a manner of indecisiveness among member states, often claimed as ‘small states’ in the face of the rivalry taking place in its backyard. Keywords: ASEAN, assertiveness, China, hedging, strategy